A tale of two extremities: A dynamic case of Covid-19 induced hypokalemia and bradycardia leading into Torsade's de pointes. (June 2021) - Navid Siddiqui, Saquib; Memon, Muhammad; Tshering, Sonam; Hasan, Tanveer; Jawed, Asheer; Kumar Jha, Pranav; Jayasekhar, Roland
Abstract: Introduction: As researchers and academics around the world scramble ahead to dissect and analyse every aspect of the SARS-CoV2 virus, one such study explored the various underlying electrolyte abnormalities that were precipitated in patients suffering from a confirmed COVID-19 infection. A significant proportion of such patients were noted to be hypokalemic. Hypokalemia can be life threatening as it is known to cause cardiac arrhythmia. Case presentation: Our encounter with said presentation was incidental. The on-call medical team was involved in a cardiac arrest call for a 74-year -old gentleman who developed torsades de pointes, Retrospective analysis of the clinical picture pointed out the fact that he was found to be persistently hypokalemic and bradycardic solely triggered as a result of COVID-19. Conclusion: Although initially thought to be a pulmonary disease but along with time extra-pulmonary manifestations of Covid-19 has demonstrated significant consequences. Electrolyte abnormalities and cardiac dysfunction are examples of such extra-pulmonary pathologies. Therefore, it is important to keep close monitoring for such abnormalities otherwise could lead into life threatening arrythmias. HIGHLIGHTS: Covid-19 is associated with cardiac conduction defects. Covid-19 is associated with hypokalemia. Hypokalemia and bradycardia can result in Torsades de pointes.